Atypical dento-alveolar fracture fixed with screws: a technical note - Shinohara, Elio Hitoshi [UNESP]; Vieira, Eduardo Hochuli [UNESP]; Garcia Júnior, Idelmo Rangel [UNESP]; Soubhia, Ana Maria Pires [UNESP]; Martini, Marcelo Zillo (Wiley-Blackwell, 2010)
Dento-alveolar process fracture is an important and common event in the dental office practice usually managed under the well-established protocols, but sometimes this kind of lesion is evaluated in the hospital emergency rooms without attention to the dental injuries. In this type of trauma, the time between the injury and the definitive resolution is essential for the treatment success, usually 1 h in cases of dento-alveolar fractures (tooth and alveolar bone). This paper describes the management of a patient with unusual dento-alveolar fracture caused by gunshot and treated using screw fixation.